Effects of principal stress rotation on the wave–seabed interactions - Wang, Zhe; Yang, Yunming; Yu, Hai-Sui (Springer Verlag, 2016)
This paper simulates the wave–seabed interactions considering the principal stress rotation (PSR) by using the finite element method. The soil model is developed within the framework of kinematic hardening and the bounding surface concept, and it can properly consider the impact of PSR by treating the PSR generating stress rate independently. The simulation results are compared with centrifuge test results. The comparison indicates that the simulation with the soil model considering the PSR can better reproduce the test results on the development of pore water pressure and liquefaction than the soil model without considering the PSR. It indicates that it is important to consider the PSR impact in simulation of wave–seabed soil interactions.